Blocking effect of benzene-like fluid transport in nanoscale block-pores. Issue 7 (3rd May 2017) - Hu, Yaofeng; Yu, Xiaochen; Tao, Jiabo; Liu, Yu; Zhao, Shuangliang; Liu, Honglai
Abstract: The flux through nanoscale pore is one of the key quantities in many processes including membrane applications and fluid separation. Whereas many efforts have been dedicated to the investigation of the fluid flux in nano-channels, the fluid transport behaviours in the block-pores, which contain distinct parts with different geometries or interactions with fluid, are still poorly understood. In this work, by combining both non-equilibrium dynamics simulation and density functional theory, we developed an efficient method for investigating the fluid flux in the block-pores, with which the fluxes of benzene in graphene block slit pores containing a hydrophobic and a hydrophilic region are thereafter investigated. We demonstrate that a region with a stronger interaction with fluid generates a bottleneck for the fluid flow, which greatly suppresses the flux in the pore even though there is no geometrical variation. By tuning the fluid-substrate interaction, the flux inside can be controlled. This study gives clues for the practical application of membrane design.